Studi Kelayakan Bisnis Dalam Prespektif Ekonomi Syariah: (Studi: Puncak Elektronik Di Kota Kendari) - Wahid Mongkito, Abdul; Mahfudz, Mahfudz; Sucitra Ika Putri, Nur; Palaguna Haana, Halber (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2021)
This study aims to determine the feasibility of puncak elektronik business feasibility studies were analyzed from legality aspects, marketing aspects, and financial aspects. As well as, sharia review of the top electronic business feasibility studies. This study uses a qualitative research type, using a sociological economic approach and using field research research methods. Data collection techniques use onservation, interview, and documentation techniques. Respondents of this study are the owner of electronic tops. The results of this study indicate that (1) in terms of legality aspects, it is feasible to run the electronic peak because it already has bisiness licenses. (2) in terms of the aspect of electronic peak marketing it is declared feasible to run because the 4P marketing strategy (product, price, place, promotion) has been implemented. (3) in terms of the financial aspect of the electronic peak it is declared feasible to run because the calculation results use the paybac period (PP) method of o.44 or 5 months 8 days shorter than the expected payback period, which is 3 years and the average rate of rerurn (ARR) result is 312% greater than the estimated profit value, which is 100%. And (4) sharia review of business feasibility studies electronic peak based on the legality aspects of marketing aspects and financial aspects in the conduct of its business does not contradict Islamic law